Short-term Persistence Performance of Equity Mutual Fund Returns: Evidence from India - Veeravel, V. (Copernican Journal of Finance & Accounting, 2024)
The present study verifies the short-term persistence performance of equity mutual fund returns. The study considers 47 equity funds’ monthly excess returns spanning from January 2000 to December 2019. The study employs prominent asset pricing models such as Jensen (1968) one-factor model, Fama-French (1993) three-factor model, and Carhart (1997) four-factor model to capture the short-term persistence of equity mutual fund returns. The results show that Jensen’s one-factor and Fama-French three-factor models are explaining a better persistence performance in the Indian context.